Variational inequality problems for total quasi-asymptotically nonexpansive mapping in Hilbert spaces - Kilicman, Adem; Mohammed, Lawan Bulama (IOP Publishing, 2018)
In this paper, we study variational inequality problems for total quasi-asymptotically nonexpansive and uniformly k-Lipschitzian mappings. Further, we propose an algorithm for solving variational inequality problems and prove the convergence result of the proposed algorithm. The results presented in this paper extend, improve and generalize some recent results announced.